Protected Areas in Nepal: The Case for Higher Entry Fees - Bardecki, Michal; Wrobel, Caroline (Economic Journal of Nepal, 2015)
The recent announcement by the Ministry of Forest and Soil Conservation of an increase the entry fees for most protected areas in Nepal has drawn a degree of criticism. This paper provides an evaluation of the decision based on past experience from other jurisdictions on the setting and administration of the pricing of access to protected areas, and a review of past studies which have provided an understanding of the willingness to pay of foreign tourists in Nepal for access to the nation’s protected areas. The higher entry fees are in line with the increasingly adopted “user pays” philosophy in the context of protected area financing. In comparable areas elsewhere entry fees tend to be significantly higher than those for Nepalese protected areas, even after the announced increases in fees. Furthermore, the entry fees generally have been far below what foreign visitors would be willing to pay. The evidence suggests that demand for access to protected areas in Nepal is price inelastic in that visitor numbers have not been negatively affected by past increases in price – a situation found in many protected areas elsewhere.The Economic Journal of Nepal, Vol. 35, No. 2, April-June 2012 (Issue N0. 138)